The effect of pH on the production and composition of short- and medium-chain fatty acids from food waste in a leachate bed reactor at room temperature - Radadiya, Pooja (2023)
This study evaluated the hydrolysis and acidogenesis of food waste at different operating pHs (uncontrolled, 5.5, 6.5, 7.5, 8.5) in a leachate bed reactor (LBR) at room temperature. LBR operation at pH 6.5–8.5 resulted in a hydrolysis yield of 718–729 g SCOD/kg VSadded, which was statistically (p ≤ 0.05) higher than that obtained at pH 5.5 (577 g SCOD/kg VSadded) and the uncontrolled pH (462 g SCOD/kg VSadded). The hydrolysis rate at pH 6.5 was the highest amongst all the pH values. Stabilization at pH at 6.5 also resulted in a high fatty acid (FA) yield of 643 g CODFA/kg VSadded. Butyrate was the main FA at the pH of 5.5–6.5, while acetate was the main FA at the pH of 7.5–8.5. At the uncontrolled pH, lactate production was the highest, indicating a shift in the microbial community from fatty-acid-producing bacteria to lactate-producing bacteria. The compositions of medium-chain fatty acids, such as caproate, were the highest at pH of 5.5.